Vitrais Religiosos: um estudo de caso na Paróquia São Luís Gonzaga - SP - Silva, Victor Augusto Pires da (2016)
The objective of this research is to understand the symbolic construction of religious stained glass, taking as a case study to Sao Luis Gonzaga Parish in São Paulo. For this, we turn to a historical context in order to locate the origins of the church and its relation to religious art. Through detailed exposition of stained glass through photography, it is perceived as the characters in the story are portrayed in art. Finally, our goal is to question whether the windows preserve the pedagogical principles when they were originally created.